Greece : Stand-By Arrangement; Review Under the Emergency Financing Mechanism. (IMF Staff Country Reports; Country Report ;, 2010)
Greece has made a strong start with the program, but challenges also remain evident. The economic response to the program has yet to play out fully. Inflation is too high. Fiscal developments are encouraging, but risks need to be addressed. A strong pension reform is essential to bolster fiscal sustainability. Liquidity problems of banks and gradual solvency erosion require continued vigilance. Confidentiality considerations are complicating effective engagement of the Policy Support Instrument. The importance of strong reforms for future growth cannot be overestimated.